Prevalence And Economic Losses Due To Bovine Tuberculosis In Cattle Slaughtered At Bodija Municipal Abattoir, Ibadan, Nigeria (2019)
Bovine tuberculosis (BTB) is a zoonotic disease responsiblefor considerable economic losses; with consequent negative impact on both public health and the livestock industry. However, the burden of this disease and associated economic losses remain un-investigated among slaughtered cattle in Ibadan, the hub of livestock activities in south-western Nigeria. A cross sectional study was conducted over a three-month period to determine the prevalence and economic losses due to BTB among slaughtered cattle at the Bodija Municipal Abattoir, Ibadan, in south-western Nigeria. Individual slaughtered cattle were purposively inspected for the presence of tuberculous lesions, and representative sample of affected organs and associated lymph nodes from the BTB suspected animals were taken. The suspected lesions were processed based on Becton Dickinson digestion and decontamination procedure and the losses due to BTB were estimated mathematically, using a formula. The BTB prevalence of 9.3 % (38/408) was obtained with a significant statistical association (P ≤ 0.05) of the disease with the breeds of cattle slaughtered. Out of the 46 visceral organs condemned: 29 (63 %) were lungs, 12 (26.1 %) livers, 4 (8.7 %) hearts and 1 (2.2 %) kidney. The total estimated annual economic loss (direct and indirect) due to BTB was estimated as Nigerian naria NGN 703,980,070 (EUR 1,725,441.4). This study revealed BTB as endemic and a major cause of concern considering its ill-health and economic effects on both humans and the livestock industry. Efforts are therefore required: to control this disease along the beef value chain in order to safeguard human and livestock health; as well as to limit the economic losses associated with its prevalence.